One-step fabrication of recycled Ag nanoparticles/graphene aerogel with high mechanical property for disinfection and catalytic reduction of 4-nitrophonel - Zhang, Yi (Environmental technology, 2019)
Fabrication of smart composites with expected removal property and excellent recycle performance for micro-pollutants including microbes and organic contaminants without formation of second-pollutants is highly desired. In this work, Ag nanoparticles (Ag NPs) homogenously loaded on graphene aerogel (GA) as Ag NPs/GA was facilely fabricated by a one-step process and the composite was characterized in detail. The bactericidal performance of the composite towards escherichia coli (E. coli) was evaluated and the catalytic activity was probed for the reduction of 4-nitrophenol (4-NP). Results showed that the composite contains about 44.4 wt% of well-dispersed Ag NPs with diameters ranging from 10 to 100 nm. Compared with the bare Ag particles or GA, Ag NPs/GA exhibited an enhanced bactericidal performance for 8-lg of E. coli cells with 100% inactivation rate and catalytic activity for 4-NP with 96.6% degradation rate, respectively. Impressively, the 100% inactivation rates for 8-lg of E. coli remained after 7 recycles and the releasing silver was negligible compared with the loaded Ag NPs. Moreover, the used Ag NPs/GA for the catalytic reduction of 4-NP can be regenerated easily by calcination in inert atmosphere. Hence, Ag NPs/GA can be regarded as a promising and cost-efficient composite for environmental remediation